Community Empowerment through Pala Waste Utilization: Ecoenzymes, Syrup, and Candied Nutmeg in Paya Village, Pesawaran District - Yasir, Angga Saputra; Suryaneta, Suryaneta; Sari, Indah Puspita; Putri, Tikarahayu; Handayani, Kiki Yuli (Amirul Bangun Bangsa, 2023)
This community engagement initiative unfolds in Paya Village, located in the Padang Cermin Subdistrict, Lampung Province, Indonesia. With a population of 1,190 individuals distributed across four hamlets, the village predominantly thrives on daily labor and agriculture, with nutmeg as a prominent crop. Organic waste generated from nutmeg fruit, particularly the husks and flesh, has been largely underutilized. This initiative, led by the PKK group, endeavors to empower the community, enhance household incomes, and address the issue of organic waste accumulation by converting nutmeg waste into value-added products. The program focuses on creating eco-enzymes, nutmeg syrup, and candied nutmeg. Capacity-building activities are central to this initiative, involving workshops, training, and educational programs. Regular evaluations highlight the program’s success in enhancing participants’ knowledge and awareness of nutmeg products.